Neurogenin3 phosphorylation controls reprogramming efficiency of pancreatic ductal organoids into endocrine cells. Issue 1 (December 2018) - Azzarelli, Roberta; Rulands, Steffen; Nestorowa, Sonia; Davies, John; Campinoti, Sara; Gillotin, Sébastien; Bonfanti, Paola; Göttgens, Berthold; Huch, Meritxell; Simons, Benjamin; Philpott, Anna
Abstract β-cell replacement has been proposed as an effective treatment for some forms of diabetes, andin vitro methods for β-cell generation are being extensively explored. A potential source of β-cells comes from fate conversion of exocrine pancreatic cells into the endocrine lineage, by overexpression of three regulators of pancreatic endocrine formation and β-cell identity, Ngn3, Pdx1 and MafA. Pancreatic ductal organoid cultures have recently been developed that can be expanded indefinitely, while maintaining the potential to differentiate into the endocrine lineage. Here, using mouse pancreatic ductal organoids, we see that co-expression of Ngn3, Pdx1 and MafA are required and sufficient to generate cells that express insulin and resemble β-cells transcriptome-wide. Efficiency of β-like cell generation can be significantly enhanced by preventing phosphorylation of Ngn3 protein and further augmented by conditions promoting differentiation. Taken together, our new findings underline the potential of ductal organoid cultures as a source material for generation of β-like cells and demonstrate that post-translational regulation of reprogramming factors can be exploited to enhance β-cell generation.